2008
DOI: 10.1016/j.chroma.2008.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of sulfonamides, tetracyclines and tiamulin in swine wastewater by solid-phase extraction and liquid chromatography–mass spectrometry

Abstract: a b s t r a c tLittle is known about the contamination level of antibiotics in swine wastewater in China. The highly complex matrix of swine wastewater, which generally has a chemical oxygen demand (COD) concentration as high as 15,000 mg/L, makes it difficult to detect antibiotics at trace levels. In this work, a highly selective and sensitive analytical method was developed for simultaneous determination of three classes of commonly used veterinary antibiotics including five sulfonamides, three tetracyclines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
92
3
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(113 citation statements)
references
References 31 publications
6
92
3
5
Order By: Relevance
“…Chlortetracycline, oxytetracycline and tetracycline were found to be used in the feeds of the two swine farms, while other antibiotics including sulfamonomethoxine, doxycycline, trimethoprim, enrofloxacin, leucomycin and florfenicol were only found in the feeds from farm S3 (Table S7). High concentrations and frequencies of tetracyclines were also found in the manure and wastewater from other swine farms in China (Ben et al, 2008;Chen et al, 2012aChen et al, , 2012bPan et al, 2011;Tong et al, 2009;Wei et al, 2011;Zhao et al, 2010), implying frequent application of these antibiotics in swine breeding in China. Dewey et al (1999) has reported that tetracyclines such as tetracycline, chlortetracycline and oxytetracycline are often fed to all ages of pigs to improve growth and prevent diseases, but included more frequently in the feeds for immature swine than for mature swine.…”
Section: Use Of Antibiotics In the Livestock Farmsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chlortetracycline, oxytetracycline and tetracycline were found to be used in the feeds of the two swine farms, while other antibiotics including sulfamonomethoxine, doxycycline, trimethoprim, enrofloxacin, leucomycin and florfenicol were only found in the feeds from farm S3 (Table S7). High concentrations and frequencies of tetracyclines were also found in the manure and wastewater from other swine farms in China (Ben et al, 2008;Chen et al, 2012aChen et al, , 2012bPan et al, 2011;Tong et al, 2009;Wei et al, 2011;Zhao et al, 2010), implying frequent application of these antibiotics in swine breeding in China. Dewey et al (1999) has reported that tetracyclines such as tetracycline, chlortetracycline and oxytetracycline are often fed to all ages of pigs to improve growth and prevent diseases, but included more frequently in the feeds for immature swine than for mature swine.…”
Section: Use Of Antibiotics In the Livestock Farmsmentioning
confidence: 99%
“…High concentrations of antibiotics have been frequently found in animal manure, such as in pig manure (Chen et al, 2012a;Jacobsen and Halling-Sorensen, 2006;Martínez-Carballo et al, 2007;Zhao et al, 2010), cattle manure (Zhao et al, 2010) and chicken manures (Karci and Balcioglu, 2009;Martínez-Carballo et al, 2007;Zhao et al, 2010) at concentrations up to hundreds of mg/kg, and in animal wastewater at concentrations up to μg/L (Ben et al, 2008;Campagnolo et al, 2002;Chen et al, 2012b;Tagiri-Endo et al, 2009;Watanabe et al, 2010). In Chinese livestock farms, most of wastewater and manure are directly or indirectly discharged into surface water or applied onto agricultural land, resulting in the contamination of antibiotics in aquatic and terrestrial environments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the major drawbacks to work with MIPs in ELISA is the absence of a reproducible and straightforward method for coating microplate wells with the material. In the literature, there are several papers describing the applications of MIPs in ELISA, [8][9][10][11][12][13][14][15] but only a few demonstrate direct application of MIPs in the assays for quantitative detection of the target analytes. [8][9]16 In one example, the surface of the microplate wells was modified with a homopolymer of 3-aminophenylboronic acid, which was imprinted with ephedrine 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Independentemente da técnica de destinação das ARSs, deve-se levar em conta as altas concentrações de nitrogênio , fósforo, sódio, cálcio, magnésio, cobre, zinco, matéria orgânica (KUNZ, 2005), antibióticos veterinários (BEN et al, 2008;COSTA et al, 2009;FRANCO et al, 2010) e patógenos (VENGLOWSKY et al, 2009;COSMANN et al, 2012), pois, em excesso, podem causar danos às plantas ou, ainda, poluir os corpos hídricos devido ao escoamento superficial e/ou à lixiviação (KUNZ, 2005). Sendo assim, GONDIM et al (2010) verificaram as diferenças entre os grupos da macrofauna edáfica em solo cultivado com maracujazeiro-amarelo com adição de biofertilizante bovino e encontraram que com irrigação de água salina e na dose de 30 mg L -1 na seca, ocasionou maior quantidade de organismos no período chuvoso.…”
unclassified